PENERAPAN TAAT ASAS KEPASTIAN HUKUM DALAM PEMBENTUKAN PERATURAN INTERNAL (HOSPITAL BY LAWS) DAN KODE ETIK RUMAH SAKIT X - Hutajulu, Maria Margaeta; Roza, Darmini; Madjid, Neni Vesna (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: The provisions of Hospital By Laws or Internal Hospital Regulations are regulated in the Decree of the Minister of Health of the Republic of Indonesia Number 772/Menkes/SK/VI/2002 concerning Guidelines for Preparing Hospital By Laws or Internal Hospital Regulations and the Hospital Code of Ethics are regulated in Government Regulation Number 47 2021 Concerning the Implementation of the Hospital Sector. This research is an analytical descriptive research. The approach used in this research is a normative juridical approach. Strict application of the principle of legal certainty in the formation of Internal Regulations (Hospital By Laws) and the Code of Ethics for Hospital including recognition of patient rights, obligations of health workers, and hospital governance. In the context of HBL, Hospital The code of ethics must reflect the values of professionalism, justice and humanity, while ensuring consistency with written legal norms.Keywords: Principle of Legal Certainty, HBL, Code of Ethics, Hospital.